Women's group therapy : creative challenges and options - Maass, Vera Sonja (Springer series, focus on women, 2006)
Extremely interesting and enlightening. Each chapter?s topics come alive and will be especially appealing to both professional and lay readers. Dr. Maass cites relevant research that informs the reader in a very understandable way.